2021
DOI: 10.1101/2021.01.17.427024
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tropism of SARS-CoV-2 for Developing Human Cortical Astrocytes

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) readily infects a variety of cell types impacting the function of vital organ systems, with particularly severe impact on respiratory function. It proves fatal for one percent of those infected. Neurological symptoms, which range in severity, accompany a significant proportion of COVID-19 cases, indicating a potential vulnerability of neural cell types. To assess whether human cortical cells can be directly infected by SARS-CoV-2, we utilized pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 45 publications
7
35
1
2
Order By: Relevance
“…Here we show that astrocytes are the main locus of infection -and possibly replication -of SARS-CoV-2 in COVID-19 patients' brains, as evidenced by the detection of the viral genome, the SARS-CoV-2 spike protein and dsRNA in both postmortem brain tissues and in vitro astrocytes. These findings are in line with recently published evidence showing that astrocytes from primary human cortical tissue and stem cellderived cortical organoids are susceptible to SARS-CoV-2 infection (Andrews et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Here we show that astrocytes are the main locus of infection -and possibly replication -of SARS-CoV-2 in COVID-19 patients' brains, as evidenced by the detection of the viral genome, the SARS-CoV-2 spike protein and dsRNA in both postmortem brain tissues and in vitro astrocytes. These findings are in line with recently published evidence showing that astrocytes from primary human cortical tissue and stem cellderived cortical organoids are susceptible to SARS-CoV-2 infection (Andrews et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Reports suggest tropism of SARS-CoV-2 to NPCs with viral proteins colocalizing with SOX2-positive neural rosettes ( Song et al, 2020 ) and NPC marker Nestin ( Mesci et al, 2020 ; Zhang et al, 2020 ). However, other reports do not support this observation ( Andrews et al, 2021 ; Ramani et al, 2020 ). This discrepancy cannot be readily attributed to the protocol for organoid differentiation, their age, incubation time with the virus and the viral dose ( Table 1 ) highlighting the need for further corroboration by independent studies with larger numbers of replications (see also Brain Organoid Models Have Started to Reveal Cellular and Molecular Mechanisms of Environmental Insults and Technological Advances Drive Progress in Brain Organoid Research and Increase Interpretability Across Studies ).…”
Section: Viral Infections With Vertical Transmission From Mother To Fetusmentioning
confidence: 70%
“…If ChP is permissive to SARS-CoV-2 brain entry, the question is which cell types within the brain may be affected by the virus. Several brain organoid studies show infection of NSCs ( Mesci et al, 2020 ; Song et al, 2020 ; Zhang et al, 2020 ), neurons ( Jacob et al, 2020 ; Mesci et al, 2020 ; Ramani et al, 2020 ; Song et al, 2020 ; Zhang et al, 2020 ; Andrews et al, 2021 ), and even astrocytes ( Jacob et al, 2020 ; Mesci et al, 2020 ; Andrews et al, 2021 ) by the novel coronavirus. Considering neurogenesis, the next focus will be on the potential infection of NSCs and newborn neurons.…”
Section: Viral Infections With Vertical Transmission From Mother To Fetusmentioning
confidence: 99%
“…417 The same has been suggested for the CNS where direct invasion of viruses into the astroglial compartment has been shown. 418,419 It has also been shown that entry into the nervous system space may happen through capillary pericyte infection by SARS-CoV-2. 420 The fact however that SARS-CoV-2 infection is not consistently found in COVID-19 patients with neurological symptoms may suggest a transient nature of CNS infection.…”
Section: Covid-19 To the Rescuementioning
confidence: 99%